Is the benefit of sequential 5-fluorouracil and daylight photodynamic therapy versus daylight photodynamic therapy alone sustained over time? – 12-month follow-up of a randomized controlled trial - Stine Regin Wiegell; Gabriella Fredman; Flemming Andersen; Peter Bjerring; Uwe Paasch; Merete Haedersdal (Photodiagnosis and Photodynamic Therapy)
Background: Since recurrences and new AKs commonly are observed after treatment long-term effects of field-directed therapies for AKs are crucial. Thus, we evaluated the 6- and 12-month efficacy and satisfaction of sequential topical 5-fluorouracil (5-FU) and daylight PDT (dPDT) with dPDT alone. Methods: In a randomized intra-individual study patients with multiple AKs in the face and scalp were treated with 4 % 5-fluorouracil cream twice daily for 7 days on one side of the scalp/face, followed by dPDT on both sides. Lesion clearance rate, lesion recurrence rate and number of new lesions were evaluated at 6- and 12-month after treatment. Results: 58/60 completed 6-month and 55/60 completed 12-month follow-up. Pre-treatment with topical 5-FU improved the long-term efficacy of dPDT, especially for moderately thick AKs, with a lesion clearance of 72 % at 12-month compared to 48 % after dPDT alone (p = 0.017). The recurrence rate at 12-month was 15 % for combination treatment and 20 % for dPDT alone (0.042). Most patients were highly satisfied with both treatments. Conclusions: Sequential treatment with short-term topical 5-FU followed by dPDT maintained a higher complete lesion clearance than dPDT alone at both 6- and 12-month follow-ups, with fewer new AKs developing after combination therapy.